PERCEPTIONS OF MEDICAL STUDENTS ABOUT THE EDUCATIONAL ENVIRONMENT AT THE START AND END OF OBSTETRICS AND GYNAECOLOGY ROTATION AND ITS IMPACT ON CAREER CHOICE - Tufail, Shazia; Baqai, Shehla; Aslam, Pakeeza; Mustafa, Nilofar; Nawaz, Qudsia; Bashir, Adeela (Journal of Ayub Medical College Abbottabad, 2021)
Background: The educational environment can influence students' learning and their attitudes towards various medical specialties, thus affecting their career choices. This study aimed to compare perceptions of medical students about educational environment at the start and end of Obstetrics and Gynaecology (O&G) rotation and to assess if these perceptions influenced their career choices. Methods: This was a Comparative analytical study carried out in the Obstetrics and Gynaecology Department, Combined Military Hospital Lahore Medical College from 1st February to 30th July 2019. Eighty-eight final year MBBS students (60 females and 28 males; average age 22±1.2 years) completed validated Dundee Ready Education Environment Measure (DREEM) questionnaire at the start and end of three weeks of O&G clinical rotation. Two questions were added post rotation to assess impact of their perceptions on career choice. Data was analysed through SPSS version 21 using independent sample t-test. Results: Mean total DREEM score was 126.68±14.17 and 127.49±15.31 out of a maximum of 200 pre and post rotation (p-value 0.001). The sub-scale which improved significantly (p-value 0.010) was Perception of Environment with average scores of 27.88±4.63 and 28.25±4.64 pre and post rotation. Majority of female students (78.7%) felt motivated for choosing O&G as a career after this rotation. Conclusion: Final-year medical students perceived the learning environment to be positive. Clinical rotation helped in improving their perception about O&G learning environment and helped female students get more inclined to choose this specialty as a career.